Implementation of anthropometric measurements in anterior teeth selection in two ethnic groups: An in vivo study - Sadananda Hota; Purnendu Bhushan; Anjana Raut; Arun K Mohanty; Debashish Mishra; Lala Wage (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to evaluate whether there is any consistent relationship between interalar distance and six maxillary anterior teeth in two ethnic groups. Materials and Methods: Two hundred subjects (Assamese 100 and Nyishi 100) of different age and sex ranging from 18 to 33 years were identified for this study. The distance between two widest points marked on the alae of nose was measured by means of sliding digital caliper. Statistical analysis of variance was the testing method to determine whether the nasal width and intercanine distance were different in various racial groups. Results: The mean nasal width dimension in Assamese group was 36.38 mm (range 28.55-50.00 mm). The mean nasal width dimension in Nyishi group was 35.73 mm (range 31.34-41.90 mm). For the nasal width, no significant difference was observed between two races. For the canine cusp tip to cusp tip distance, the mean value of Assamese subjects was 43.63 mm (range 39.02-50.02 mm), whereas the Nyishi presented 41.77 mm (range 36.69-47.05 mm). Conclusion: For the two racial groups studied, the measurements of the interalar width showed a weak correlation with the canine to canine distance, not sufficiently high to be used as a predictive factor. It suggests to select wider artificial teeth. Practitioners can use ethnic norms as guides, not absolute values.